The Contingent Valuation Methodas an Instrument for the Environmental Valuation of Water Resources (London Journal of Research In Humanities and Social Sciences, 2023)
The contingent valuation method is widely known in the academic world for being a simple and flexible non-market estimation method, which is widely used in environmental cost-benefit analysis and in environmental impact assessment schemes. Its empirical application is almost a standard issue at a global level, however, little has been discussed about the limitations, difficulties and potential it has for the valuation of water resources. In this line, the article seeks to identify the main water resources studied, the econometric techniques used, the objectives and conclusions reached in the studies that cover this topic. To achieve this, anexhaustive bibliographic review is proposed using the PRISMA methodology, in the Scopus, Scielo and Ebsco repositories, emphasizing publications made in Spanish, Portuguese and English worldwide. The results show a tendency to analyze the services of drinking water, wetlands and lakes, in which there is a prevalence of the binomial logit and probit models as econometric instruments and where the aim is essentially to estimate the willingness to pay.
Keywords: willingness to pay; hydroecological systems; econometric models; total value